Engineered biomaterials to mitigate growth factor cost in cell biomanufacturing. (June 2019) - Xie, Angela W.; Murphy, William L.
Abstract: Successful commercialization of cell-based therapies depends on technologies and processes that support scalable, reproducible, and economical cell biomanufacturing. Currently, derivation of target therapeutic cell types from primary cells and stem cells often involves lengthy expansion and differentiation processes that use substantial quantities of recombinant growth factors (GFs) and cytokines. Engineered biomaterials that can regulate GF delivery, activity, and signaling offer promise as tools to enable more efficient GF usage in cell culture. This review discusses emerging design strategies for GF-regulating biomaterials and how such materials may be applied to mitigate growth factor cost in cell biomanufacturing.